(untitled) (Research, Society and Development, 2021)
Chronic pelvic pain is a painful process that interferes with women’s daily activities, requiring clinical or surgical interventions. The aim of this study is to present the repercussions of chronic pelvic pain in women assisted in primary care. This is a cross-sectional and quantitative study, conducted with women assisted in three primary care units and one specialized outpatient clinic located in São Luís, Maranhão, Brazil, from May to October 2018. A structured questionnaire was used. From the results, the following prevalence on the profile of women stood out: age from 18 to 23 years (18%), complete high school (46%), unemployment (43.3%), women with arterial hypertension and diabetes (23%), with pain duration for days (60%), pain scale from 7 to 10 (73%), negative influence of pain on family relationships (63%), with insomnia (59%), anxiety (78%) and depression (32%). There was a predominance of young women, with medium schooling, unemployed, with dysfunctional bowel elimination pattern, with persistent and intense pain and dyspareunia. Chronic pelvic pain has impaired the social life, quality of life and psychological health of the participants, which indicates the need for multidisciplinary health interventions.